2016
DOI: 10.11157/anzswj-vol25iss2id81
|View full text |Cite
|
Sign up to set email alerts
|

The Canterbury Earthquakes and refugee communities

Abstract: The Canterbury earthquakes and subsequent aftershocks have presented a number of challenges for resettled refugee communities living in this region. These events highlight the need to recognise the diversity within culturally and linguistically diverse (CALD) populations for effective disaster preparedness and response initiatives. This paper presents a pilot study of focus groups conducted with the Ethiopian, Afghan and Bhutanese communities about their perspectives and responses to this particular disaster. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Given that the focus groups were conducted in English, this study did not account for the perspectives of community members who are not fluent in English. Past studies have demonstrated that non-English speakers and those from minority cultures, such as refugees and non-English speaking immigrant groups, hold different perspectives pertaining to disaster preparedness and response, and employ unique strategies to buffer against hazard event impacts and recover from disasters (Chamlee-Wright and Storr 2010; Eisenman et al 2009; Marlowe and Lou 2016). Future studies are needed to solicit the perspectives of communities who were not part of this research study.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Given that the focus groups were conducted in English, this study did not account for the perspectives of community members who are not fluent in English. Past studies have demonstrated that non-English speakers and those from minority cultures, such as refugees and non-English speaking immigrant groups, hold different perspectives pertaining to disaster preparedness and response, and employ unique strategies to buffer against hazard event impacts and recover from disasters (Chamlee-Wright and Storr 2010; Eisenman et al 2009; Marlowe and Lou 2016). Future studies are needed to solicit the perspectives of communities who were not part of this research study.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Again, there is considerable diversity across the various refugee populations in New Zealand, but the practice among resettlement agencies of geographically co-locating members of the same refugee communities allows for at least the potential for those communities to maximise (or to develop) levels of bonding capital to provide mutual support and to validate and reinforce cultural norms and practices among the second generation. This form of support is vital, not only in terms of reinforcing feelings of belonging, but the literature from the Canterbury earthquakes has demonstrated the role of ethnic communities in responding to and supporting one another in a large-scale disaster (Osman et al 2012;Marlowe & Lou 2013). However, strong bonding capital can also be problematic when there is limited bridging and linking capital as it can potentially have negative implications through local power structures that reinforce oppressive practices.…”
Section: Housingmentioning
confidence: 99%
“…Despite the growing number of Chinese migrants living in Auckland's super-diverse urban environment, to the authors' knowledge, no research to date has been conducted to understand their perceptions of disaster risk and experiences in the face of hazards and disasters. In the New Zealand context, the limited literature on migrants in relation to disasters and disaster risk reduction have focused on Southeast Asians, Pacific Peoples or refugees (Marlowe and Lou, 2013;Marlowe, 2015;Uekusa and Matthewman, 2017;Marlowe et al, 2018;Grayman et al, 2019;Odiase et al, 2020). Given the paucity of information pertaining to Asian, specifically Chinese, migrants in the face of disasters, the presented qualitative descriptive study aimed to understand aspects of Chinese migration in relation to disasters and explore strategies for migrantinclusive disaster risk reduction.…”
Section: Introductionmentioning
confidence: 99%